2016
DOI: 10.17221/188/2015-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of weather derivatives as a hedge against the weather risk in agriculture

Abstract: Abstract:Weather aff ects the economies worldwide and all economic sectors are to some extent weather sensitive. Agriculture is traditionally highly weather sensitive. While the catastrophic impact of weather has been long recognized, studied and managed the non-catastrophic weather risk gains in importance as the climate change becomes more pronounced. Weather derivatives provide a fl exible management solution for the non-catastrophic weather risk. Th e paper presents weather derivatives as a new weather ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
8
0
3
Order By: Relevance
“…Besides the risk reduction function which can also be conducted by weather index issuance, weather derivatives eliminate possibilities of moral hazard and adverse selection since the compensation totally depends on the weather index at maturity. Ivana et al (2016) proved this statement by reviewing existing literature about the effectiveness of the application of weather derivatives and weather insurance in agriculture. They observed that geographical location and period covered by the derivatives are the main reason for effectiveness volatility, which refers to the range of price-volatility reduction of agricultural products.…”
Section: Review Of the Previous Studymentioning
confidence: 92%
See 1 more Smart Citation
“…Besides the risk reduction function which can also be conducted by weather index issuance, weather derivatives eliminate possibilities of moral hazard and adverse selection since the compensation totally depends on the weather index at maturity. Ivana et al (2016) proved this statement by reviewing existing literature about the effectiveness of the application of weather derivatives and weather insurance in agriculture. They observed that geographical location and period covered by the derivatives are the main reason for effectiveness volatility, which refers to the range of price-volatility reduction of agricultural products.…”
Section: Review Of the Previous Studymentioning
confidence: 92%
“…Weather derivatives are highly correlated with the agriculture industry because both the quantity and quality of crop yield are significantly affected by weather (Ivana et al, 2016). Researchers have been testing the effectiveness of weather derivatives for the agriculture industry in different regions during the past 20 years.…”
Section: Review Of the Previous Studymentioning
confidence: 99%
“…Należy jednocześnie pamiętać, że poza pozyskiwaniem środków finansowych w rolnictwie występuje wiele innych -wymienionych wcześniej -przeszkód i ograniczeń rozwoju działalności innowacyjnej. Zatem same rynki kapitałowe nie będą w stanie przezwyciężyć wszystkich czynników hamujących rozwój w tym zakresie 75 . Rozwiązaniem tej problematycznej sytuacji jest doprowadzenie na obszarach wiejskich do równowagi pomiędzy popytem i podażą usług finansowych.…”
Section: Bariery W Pozyskiwaniu Finansowania Przez Rolnikówunclassified
“…Due to ethical problems such as adverse selection (i.e., due to information asymmetry) in traditional agricultural insurance [20], recent research has mainly focused on weather index insurance [21,22]. However, insurance is mostly used for catastrophic events, whereas derivatives provide a more flexible risk management tool for non-catastrophic weather risks [23,24]. Gao et al [25] found that using options as a hedging strategy can help retailers improve their expected profits.…”
Section: Literature Reviewmentioning
confidence: 99%